2019
DOI: 10.1371/journal.ppat.1008213
|View full text |Cite
|
Sign up to set email alerts
|

Novel cholinesterase paralogs of Schistosoma mansoni have perceived roles in cholinergic signalling and drug detoxification and are essential for parasite survival

Abstract: Cholinesterase (ChE) function in schistosomes is essential for orchestration of parasite neurotransmission but has been poorly defined with respect to the molecules responsible. Interrogation of the S. mansoni genome has revealed the presence of three ChE domain-containing genes (Smche)s, which we have shown to encode two functional acetylcholinesterases (AChE)s (Smache1 –smp_154600 and Smache2 –smp_136690) and a butyrylcholinesterase (BChE) (Smbche1 –smp_125350). Antibodies to recombinant forms of each SmChE … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(41 citation statements)
references
References 75 publications
5
36
0
Order By: Relevance
“…Surface-exposed proteins and secreted proteins are effective targets for vaccine development in schistosomes due to their capacity for interaction with host antibodies [17,18]. In this regard, SmChEs are promising candidates as we have shown in previous immunolocalization studies in S. mansoni that SmAChE1, SmBChE1 and SmAChE2 are expressed in the tegument of adult worms and schistosomula and proteomic analysis of S. mansoni ES products has confirmed the presence of SmAChE1 and SmBChE1 [6]. Further, RNAi-mediated silencing of all 3 SmChE genes, both individually and in combination, significantly decreased schistosomula viability in vitro and parasite survival in vivo [6], implying that these genes are essential for proper worm development and function.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Surface-exposed proteins and secreted proteins are effective targets for vaccine development in schistosomes due to their capacity for interaction with host antibodies [17,18]. In this regard, SmChEs are promising candidates as we have shown in previous immunolocalization studies in S. mansoni that SmAChE1, SmBChE1 and SmAChE2 are expressed in the tegument of adult worms and schistosomula and proteomic analysis of S. mansoni ES products has confirmed the presence of SmAChE1 and SmBChE1 [6]. Further, RNAi-mediated silencing of all 3 SmChE genes, both individually and in combination, significantly decreased schistosomula viability in vitro and parasite survival in vivo [6], implying that these genes are essential for proper worm development and function.…”
Section: Discussionmentioning
confidence: 65%
“…A recent study by us [6] has documented the existence of three SmChE paralogs (two acetylcholinesterases -smache1 and smache2 -and one butyrylcholinesterase -smbche1) and we showed that each molecule localized to the tegument of adults and schistosomula and demonstrated, through RNAi-mediated suppression in vitro and in vivo, that each paralog was essential to parasite survival. We also reported a significant reduction in the glucose-scavenging ability of silenced parasites, providing evidence for the involvement of tegumental AChE in the mediation of exogenous glucose uptake, which has also been documented by other studies [10][11][12].…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations